Europe. Issue 3 (4th May 2019) - Jones, Erik
Abstract : Romania Confronts Its Communist Past: Democracy, Memory, and Moral Justice Vladimir Tismaneanu and Marius Stan. Cambridge: Cambridge University Press, 2018. £75.00. 205 pp. Time and Power: Visions of History in German Politics, from the Thirty Years' War to the Third Reich Christopher Clark. Princeton, NJ: Princeton University Press, 2019. £24.00/$29.95. 293 pp. The Responsive Union: National Elections and European Governance Christina J. Schneider. Cambridge: Cambridge University Press, 2018. £75.00. 345 pp. Close to Home: Local Ties and Voting Radical Right in Europe Jennifer Fitzgerald. Cambridge: Cambridge University Press, 2018. £75.00. 247 pp. Europe's Future: Decoupling and Reforming Sergio Fabbrini. Cambridge: Cambridge University Press, 2019. £16.99. 170 pp.